Pramipexole in addition to mood stabilisers for treatment-resistant bipolar depression: the PAX-BD randomised double-blind placebo-controlled trial - Hamish McAllister-Williams; Nicola Goudie; Lumbini Azim; Victoria Bartle; Michael Berger; Chrissie Butcher; Thomas Chadwick; Emily Clare; Paul Courtney; Lyndsey Dixon; Nichola Duffelen; Tony Fouweather; et al. (Health Technology Assessment)
Background There are limited options currently recommended in National Institute for Health and Care Excellence guidelines for the treatment of bipolar depression. Pramipexole has been shown to improve mood symptoms in two small pilot studies in such patients. Objectives Primary: to evaluate the clinical effectiveness of pramipexole versus placebo alongside routine mood-stabilising medications over 12 weeks in patients with treatment-resistant bipolar depression. Secondary: evaluate the impact of pramipexole on mood and anxiety, psychosocial function, cost-effectiveness, and safety and tolerability over 48 weeks. Design Multicentre, randomised, placebo-controlled trial of pramipexole versus placebo in addition to standard-of-care mood stabilisers. Clinicians, researchers and participants were blinded throughout the duration of the study. Pre-randomisation stage (to adjust antipsychotics or commence mood stabilisers where required) before randomisation. Weekly online assessments of mood and anxiety from randomisation to week 52, with psychosocial function, quality of life and healthcare resource utilisation assessments conducted at regular intervals. Setting Twenty-one National Health Service trusts and Health Boards across England and Scotland. Participants Patients aged 18 years and over with a diagnosis of treatment-resistant bipolar depression currently under secondary care mental health services. Aim to randomise 290 participants. Interventions Pramipexole or matched placebo orally once daily, titrated from 0.25 mg to maximum of 2.5 mg (salt weight) depending on efficacy and tolerability. Main outcome measures Depression – Quick Inventory for Depressive Symptomology; anxiety – Generalised Anxiety Disorder-7-item scale; psychosocial functioning – Work and Social Adjustment Scale; hypomania/mania – Altman Self-rating Scale of Mania; tolerability – Treatment Satisfaction Questionnaire for Medication; well-being and quality of life – EuroQol-5 Dimensions, five-level version, ICEpop CAPability measure for Adults and Oxford CAPabilities questionnaire-Mental Health tools. Results Thirty-nine participants randomised (18 to pramipexole and 21 to placebo) with 36 providing data for the primary analysis. Pramipexole led to greater reductions in depressive symptoms at 12 weeks compared to placebo [4.4 (4.8) vs. 2.1 (5.1)]: a medium-sized (d = −0.72) but not statistically significant difference (95% confidence interval −0.4 to 6.3; p = 0.087). There were some statistically significant positive effects of pramipexole on secondary outcomes (reduction in depressive symptoms at 36 weeks, response and remission rates at trial exit, psychosocial function). Pramipexole was associated with an increased rate of hypomania/manic symptoms, but this appeared to be reduced by coadministration with an antipsychotic. General tolerability of pramipexole was good. There were significant annual gains in health-related quality of life and capability-well-being and tendency towards reduced health and social care costs. Limitations Small sample size and variable follow-up period due to recruitment during COVID-19 pandemic and the trial closing early. Participants limited to those in secondary care mental health services. All assessments only available in English. Conclusions No change in clinical practice can be recommended as there was not a significant difference between pramipexole and placebo on the primary efficacy outcome measure. However, there was evidence of positive effects of pramipexole on mood, psychosocial function and quality of life. Future work Replication in a larger population and research to investigate the impact of coadministration of antipsychotics alongside pramipexole. Trial registration This trial is registered as ISRCTN72151939 and EudraCT 2018-2869-18. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 16/154/01) and is published in full in Health Technology Assessment; Vol. 29, No. 21. See the NIHR Funding and Awards website for further award information. Plain language summary Patients with bipolar disorder have symptoms (depression or elevated mood) around 50% of the time and mostly these are depressive. There are few recommended treatments for bipolar depression, they do not always work, and often come with side effects like weight gain and drowsiness. There is a suggestion that pramipexole (currently used to treat Parkinson’s disease) may help treat bipolar depression. The PAX-BD trial aimed to test this, as well as seeing if it is safe and cost-effective over 48 weeks. Those eligible for the trial were randomly allocated to receive either pramipexole or placebo. Neither the treating team nor the participants knew which treatment they were receiving. Unfortunately, only 39 participants entered the trial due to the trial being closed early. While pramipexole did lead to a greater reduction in depressive symptoms compared to placebo at 12 weeks, the difference was not statistically significant, possibly due to there being too few participants in the trial. However, there were some statistically significant beneficial effects of pramipexole on mood, everyday functioning and quality of life later in the trial. On the downside, pramipexole appeared to increase the risk that participants experienced symptoms of elevated mood. There was evidence that pramipexole may be a cost-effective treatment. However, because of the trial being small in size, the results are not definitive and we cannot conclude that pramipexole should routinely be used for people with bipolar depression. Further research is required to give a clearer answer. A patient and public involvement group worked on the trial and provided valuable input into its design and conduct, and we learnt more about how such input can be improved in future trials. We also learnt more about what can help and hinder people taking in part in studies like PAX-BD. Scientific summary Background Patients with bipolar disorder are symptomatic around 50% of the time, the vast majority of which relates to depressive symptoms. Current National Institute for Health and Care Excellence (NICE) guidelines for the management of bipolar depression (BD) include just three medication options: lamotrigine, quetiapine and olanzapine (with or without fluoxetine). Quetiapine and olanzapine are often poorly tolerated due to weight gain and sedation. Lamotrigine has a relatively small effect size and requires slow dose titration. British Association for Psychopharmacology (BAP) guidelines include a fourth option: lurasidone. However, BD often does not respond to these options leading patients to suffer from ‘treatment-resistant bipolar depression’ (TRBD). Rates of TRBD are unknown, however, around 50% of patients remain depressed at 6 months, and 30% at a year, because of treatment non-response, intolerance or non-acceptance. In addition, around 70% of currently depressed bipolar disorder patients in the UK are on at least one antidepressant despite little evidence that they are effective. Pramipexole is currently used to treat patients with Parkinson’s disease and has been shown to improve depressive symptoms in these patients, with two small pilot randomised controlled trials in BD also being positive. Objectives Primary objective To evaluate the clinical effectiveness of pramipexole versus placebo alongside standard mood-stabilising medication, over 12 weeks, in the management of TRBD. Secondary objectives To examine the impact of pramipexole on mood and anxiety symptoms, psychosocial function (over 48 weeks), and pleasure (over 12 weeks). To examine the rate of known possible side effects of pramipexole (switching to mania and occurrence of impulse control disorders) as well as tolerability by reviewing rates of adverse events (AEs), serious adverse events (SAEs) and suspected unexpected serious adverse reactions (SUSARs), and overall acceptability of pramipexole. To examine the impact of pramipexole on quality of life, well-being, health and social care and broader societal costs of participants randomised to either pramipexole or placebo, to assess cost-effectiveness. Methods Randomised, double-blind, placebo-controlled trial, conducted within secondary care settings in 21 NHS Trusts and Health Boards across England and Scotland. The trial included two stages: pre-randomisation to adjust antipsychotics and commencing mood-stabilising medication (where required) and ensuring participant engagement with study procedures, prior to randomisation. Eligibility criteria Inclusion criteria: pre-randomisation stage Under secondary care mental health services. Decision made by the patient’s clinical team that a change in medication is indicated. Current diagnosis of bipolar disorder (type I or II). Currently meeting criteria for a major depressive episode with a Quick Inventory of Depressive Symptoms, Self-Rated (QIDS-SR) score > 10. Suffering from TRBD defined as the failure (non-response, intolerance and/or refused/clinically not indicated) of ≥ 2 NICE or BAP recommended mediations for BD (quetiapine, olanzapine, lamotrigine or lurasidone) in the current episode of depression. Aged 18 or over. Willing and able to provide written informed consent. Able to follow the trial prescription instructions and manage 8 week supplies of trial medication. If female and of child-bearing potential, must have a negative pregnancy test [urine beta-human chorionic gonadotropin (β-hCG)] and required to use a highly effective contraceptive method throughout the trial. Exclusion criteria: pre-randomisation stage Severe substance use disorder. Current psychotic symptoms. History of retinal disease. Current symptoms or significant concerns around cardiovascular disease. History of significant renal disease. Any known sensitivity to trial drug including its excipients. Current or planned pregnancy during the trial period, or breastfeeding. Starting specific psychotherapy from 4 weeks before randomisation through to week 12 post randomisation. Currently taking part in another clinical trial that would interfere with the outcomes of PAX-BD. Confirmed diagnosis with potential confounding factors such as Parkinson’s disease or restless leg syndrome. Significant clinical concern regarding impulse control behaviours. Inclusion criteria: randomisation stage Been in pre-randomisation stage for a minimum of 23 calendar days. Currently depressed (QIDS-SR > 10). Minimum of two telephone/tele- or videoconference calls with a trial central research assistant (RA) team and two online weekly symptom ratings completed during the pre-randomisation stage. On mood-stabilising medication (lithium, valproate, carbamazepine, lamotrigine). Not on an antipsychotic. These criteria were amended during the trial to allow antipsychotics within specified dosing limits. All regular psychotropic medication at a stable dose ≥ 4 weeks. Additionally, if taking lamotrigine, quetiapine, olanzapine or lurasidone, this must have been at the current dose or higher for ≥ 3 months. If female and of child-bearing potential, a negative urine β-hCG test and using a highly effective contraceptive method. Willing and able to confirm written informed consent at the point of randomisation. Exclusion criteria: randomisation stage As per pre-randomisation stage including. Psychotic symptoms over the preceding 4 weeks. Any deterioration in physical or mental health since pre-randomisation leading to a clinical concern to proceed. Electroconvulsive therapy in the last 28 days. Any concern regarding the patient’s ability to remain engaged in the trial. Intervention Randomisation (1 : 1) to pramipexole or matched placebo was carried out using Sealed Envelope™, Sealed Envelope Ltd, UK (a central, secure, 24-hour web-based randomisation system with concealed allocation). Trial medication taken orally once daily. Dose up-titrated 0.25 mg every 3 days to a maximum of 2.5 mg (salt weights) depending on acceptability and tolerability over 4 weeks. The achieved dose then fixed through to week 12 and subsequently flexibly adjusted based on response and tolerability for up to 48 weeks. Medication down-titrated 0.25 mg every 3 days at the end-of-trial involvement, unless participant switched to open-label pramipexole prescribed by their local clinical team, or they were known to have been taking placebo. Outcome measures Primary outcome measure Quick Inventory of Depressive Symptoms, Self-Rated score at 12 weeks post randomisation. Secondary outcome measures Weekly QIDS-SR and Generalised Anxiety Disorder-7 scores. Snaith–Hamilton Pleasure Scale at baseline and weeks 6 and 12. Work and Social Adjustment Scale at weeks 6, 12, 24, 36 and 48. Risk of mania (assessed weekly using the Altman Self-rating Scale of Mania), psychosis or impulse control disorders (using the Questionnaire for Impulsive–Compulsive Disorders in Parkinson’s Disease – Rating Scale at baseline and weeks 6, 12 and 4 weekly thereafter). Gold-standard observer-rated scales (Montgomery–Åsberg Depression Rating Scale, Quick Inventory of Depressive Symptoms, Clinician-Rated and Young Mania Self-Rating Scale) at baseline and week 12 to facilitate comparison with other studies. Side effects and overall acceptability using the Treatment Satisfaction Questionnaire for Medication at weeks 6, 12 and then 4 weekly thereafter. Tolerability examined by reporting rates of AEs, SEAs and SUSARs. Adherence to medication examined using dose taken as reported during RA contacts. Quality of life, well-being, health and social care and broader societal costs of participants were examined (see health economic analysis below). Sample size A 30% dropout during pre-randomisation stage was predicted based on the BALANCE study (Lithium plus valproate combination therapy versus monotherapy for relapse prevention in bipolar I disorder), and post randomisation a 20% dropout by 12 weeks based on the CEQUEL study (Comparative economic evaluation of quetiapine plus lamotrigine combination vs quetiapine monotherapy (and folic acid vs placebo) in patients with bipolar depression). Power calculation based on a two-sample t-test at 12 weeks detecting a 3-point difference in QIDS-SR between drug and placebo (at p < 0.05) with a standard deviation (SD) of 7 (based CEQUEL study data). For 90% power, 232 (116 per arm) participants were required to complete the trial meaning a sample size of 290 at randomisation and an initial population of 414 recruited to the pre-randomisation stage. Subsequently, a revised calculation was done based on recent data suggesting a more appropriate minimal clinical important difference of 4 QIDS-SR points, rather than 3, and early observations of dropout rates in both pre-randomisation and randomisation stages around 10%. This produced estimated required sample sizes of 126 participants to recruit, 112 to randomise and 100 to reach the 12-week primary outcome time point for 80% power. Statistical methods Primary outcome: QIDS-SR at week 12 used analysis of covariance (ANCOVA) to compare treatment arms covarying for baseline score. A two-sided significance level of p < 0.05 was used throughout. Unadjusted analysis, including the use of the t-test, or further related regression or ANCOVA methods were also undertaken. Secondary outcomes were analysed in a manner analogous to the primary outcome. As a result of the early closure of the trial and hence reduced sample size and not all participants followed up to 48 weeks, additional analysis was limited. Health economic analysis The incremental cost-effectiveness of pramipexole in comparison to placebo was assessed over 12 and 48 weeks from health and social care, and broader societal perspectives. The Health Economics Questionnaire (HEQ) captured health and social services utilisation and broader societal costs (in GBP, year 2020–1). The EuroQol-5 Dimensions, five-level version captured health-related quality of life (HRQoL) and was used to calculate quality-adjusted life-years gained as the primary outcome measure. The ICEpop CAPability measure for Adults and Oxford CAPabilities questionnaire-Mental Health (OxCAP-MH) capability well-being measures were used to calculate capability-weighted life-years gained as secondary outcome measures. Health economic data were collected at pre-randomisation, randomisation (baseline), and at weeks 12, 24, 36 and 48 for those who reached these time points. Any baseline imbalance between groups was adjusted statistically, data missingness was handled using multiple imputation, and uncertainty in the results estimated using bootstrapping and sensitivity analyses. Qualitative study Semistructured interviews with participants and healthcare professionals (HCPs) were conducted by central researchers via telephone to investigate barriers and facilitators to recruitment and retention of participants. Interviews were audio-recorded and outsourced to UK Transcription for transcribing. Fifteen HCPs and 11 randomised participants were interviewed. Interpretation of the transcripts was guided by an a priori framework of subthemes from a meta-analysis of studies in depression. Transcripts were independently coded by researchers using NVivo Release 1.6.1 (QSR International, Warrington, UK), reviewed by the wider qualitative team and modified on an ongoing basis. Subthemes were inductively revised, and emergent themes added per recurring discussions. Finally, 120 codes and 11 subthemes were attributed to 3 key themes: Barriers, Facilitators and Suggestions for Future Improvement. Results Fifty-one participants were recruited to pre-randomisation of whom 39 progressed to randomisation (dropout rate = 24%). Completion rates for self-rated online scales were around 80%. Thirty-six participants provided primary outcome data at 12 weeks and comprised the analysis population (drop-out rate = 7.7%), 16 in the pramipexole [2.18 mg/day (0.58) mean (SD)] and 20 in the placebo arms [2.25 mg/day (0.55)]. Despite the small sample size, the two arms were well matched on demographics, illness characteristics and current medication except that the pramipexole arm had a lower QIDS-SR baseline score at randomisation [pramipexole = 15.1 (5.2) vs. placebo = 17.3 (4.7): mean (SD)]. At 12 weeks, the reduction in QIDS-SR score from baseline was twice as high in the pramipexole arm compared with the placebo arm [4.4 (4.8) vs. 2.1 (5.1)]. However, ANCOVA adjusting for baseline differences in QIDS-SR was not significant [95% confidence interval (CI) −0.4 to 6.3; p = 0.0865]. Observation of the data suggested that the peak effect of the drug may have occurred beyond 12 weeks. ANCOVA demonstrated a significant advantage of 6.28 points lower for pramipexole at 36 weeks post randomisation. Similarly, while there was no significant difference in response (QIDS-SR reduction from baseline > 50%) and remission (QIDS-SR score ≤ 5) at 12 weeks, there was an advantage of pramipexole for response (46% vs. 6%; p = 0.026) and remission (31% vs. 0%; p = 0.030) rates at exit from the trial. Secondary analysis indicated significant improvements in psychosocial function at 36 and 48 weeks. There were decreases in anxiety symptoms at 36 weeks (p = 0.087) and an increase in the ability to experience pleasure at 6 weeks (p = 0.062) for participants in the pramipexole arm was not significant. Pramipexole was associated with a significant increase in manic/hypomanic symptoms at 12 weeks, but there was no significant increase in impulse control symptoms (though a higher proportion of participants in the pramipexole vs. placebo arm experienced at least one AE related to impulse control problems). There was one SAE in the pramipexole arm assessed as related to the study medication: mania that led to hospitalisation. Of 290 AEs occurring across both treatment arms, 265 (91%) required no action, 22 (8%) had treatment interrupted/dose reduced and 3 (1%) had Investigative Medicinal Product withdrawn. There were more mild and moderate AEs in the pramipexole arm, mostly of known psychiatric, nervous system and gastrointestinal side effects. Overall, tolerability and acceptability of study medication were similar between treatment arms. Around half of the randomised participants were taking an antipsychotic. Comparing those who were and were not taking one in combination with pramipexole, it appears that the reduction in depressive symptoms was similar, but the severity of hypomanic symptoms may have been less. Health economic analysis showed significant increase in HRQoL and capability well-being, and tendency towards reduced health and social care costs with high probability (70–90%) of cost-effectiveness for all health economic outcome measures over 48 weeks from the health and social care perspective. Sensitivity analyses confirmed the main findings. Qualitative analysis identified barriers to recruitment and retention including the complexity of BD, difficulty accessing eligible participants, inadequate research prioritisation and the COVID-19 pandemic. Participants’ concerns included receiving placebo, side effects of pramipexole, the burden of managing trial medication, using technology and/or engaging with safety monitoring for 48 weeks. Facilitators included positive relationships with care teams, central team support, responsive protocol amendments, and a strong desire for effective treatment. Lessons for future trials using semiremote methodology include using mass trial promotion strategies, reducing patient burden and fostering greater collaboration between trial staff and clinicians. The trial was conducted during the COVID-19 pandemic and was terminated early due to funding reasons. Therefore, the sample size was much more limited, and the follow-up of some participants was shorter than planned. Conclusions No change in clinical practice can be recommended as there was not a significant difference between pramipexole and placebo on the primary efficacy outcome measure. This may have resulted from the early closure of the study and hence small sample size. Despite this, there were suggestions of positive effects of pramipexole on mood, psychosocial function and quality of life. However, use of the medication was complicated by the need for complex dose titration and high rates of hypomanic and impulse control symptoms, which would make implementation in routine practice challenging. Further research is required to definitively address whether pramipexole is an effective safe and cost-effective treatment for TRBD. In addition, further studies should explore the impact of coadministration of an antipsychotic alongside pramipexole. Trial registration This trial is registered as ISRCTN72151939 and EudraCT 2018-2869-18. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 16/154/01) and is published in full in Health Technology Assessment; Vol. 29, No. 21. See the NIHR Funding and Awards website for further award information.